PENANAMAN KEDISIPLINAN SISWA MELALUI SHALAT DHUHA DI MTs NEGERI 11 JOMBANG - Fatikah, Noor; Linda Wahyuni, Ervin (ILJ: Islamic Learning Journal, 2023)
Discipline is a very absolute thing in human life, because a human being without strong discipline will damage the joints of his life, with the value of discipline, every individual person can carry out his daily duties and responsibilities well, successfully, and in accordance with programmed plan.Discipline ??of students needs to be instilled in educational institutions to form a strong character in carrying out educational and learning activities.This research was conducted at MTs Negeri 11 Jombang. The objectives achieved in this study are to describe the reality of student discipline at MTs Negeri 11 Jombang and the role of teachers in improving student discipline through inculcating disciplinary values ??at MTs Negeri 11 Jombang. Thisstudy used a qualitative method with aqualitative descriptive approach. The technique of collecting data used the methods of observation, interviews, and documentation. Data analysis using an interactive model with the stages of data reduction, data presentation, and conclusion or verification.The results of this study are the reality of student discipline at MTs Negeri 11 Jombang, every morning before KBM perform dhuha prayers in congregation, while the teacher's role is improve student discipline through inculcating disciplinary ??at MTs Negeri 11 Jombang. and apply, guide, provide advice, provide examples, convey, and also evaluate. Supporting and inhibiting factors in inculcating discipline: a) Supporting factors, namely: the availability of facilities and infrastructure, absence, encouragement and the theacher council, b) Inhibiting factors, namely: the existence of a pandemic, the number of which coincides with exams, the capacity of the mosque inadequate.